Relationships Between Familial HIV/AIDS and Symptoms of Anxiety and Depression: The Mediating Effect of Bullying Victimization in a Prospective Sample of South African Children and Adolescents - Boyes, Mark; Cluver, L. (Springer New York LLC, 2015)
South African children and adolescents living in HIV/AIDS-affected families are at elevated risk of both symptoms of anxiety and depressive symptoms. Poverty and HIV/AIDS-related stigma are additional risk factors for these negative mental health outcomes. Community level factors, such as poverty and stigma, are difficult to change in the short term and identifying additional potentially malleable mechanisms linking familial HIV/AIDS with mental health is important from an intervention perspective. HIV/AIDS-affected children are also at increased risk of bullying victimization. This longitudinal study aimed to determine whether prospective relationships between familial HIV/AIDS and both anxiety symptoms and depressive symptoms operate indirectly via bullying victimization. Adolescents (M = 13.45 years, 56.67 % female, n = 3,515) from high HIV-prevalent (>30 %) communities in South Africa were interviewed and followed-up one year later (n = 3,401, 96.70 % retention). Census enumeration areas were randomly selected from urban and rural sites in two provinces, and door-to-door sampling included all households with a resident child/adolescent. Familial HIV/AIDS at baseline assessment was not directly associated with mental health outcomes 1 year later. However, significant indirect effects operating via bullying victimization were obtained for both anxiety and depression scores. Importantly, these effects were independent of poverty, HIV/AIDS-related stigma, and baseline mental health, which highlight bullying victimization as a potential target for future intervention efforts. The implementation and rigorous evaluation of bullying prevention programs in South African communities may improve mental health outcomes for HIV/AIDS-affected children and adolescents and this should be a focus of future research and intervention.